Feasibility and effectiveness of cardiac telerehabilitation for older adults with coronary heart disease: A pilot randomized controlled trial - Su, Jing Jing; Wong, Arkers Kwan Ching; He, Xi-Fei; Zhang, Li-Ping; Cheng, Jie; Lu, Li-Juan; Lan, Lan; Wang, Zhaozhao; Lin, Rose S Y; Batalik, Ladislav (Contemporary clinical trials communications, 2024)
BACKGROUND: Cardiac rehabilitation is a beneficial multidisciplinary treatment of exercise promotion, patient education, risk factor management, and psychosocial counseling for people with coronary heart disease (CHD) that is underutilized due to substantial disparities in access, referral, and participation. Empirical studies suggest that cardiac telerehabilitation (CTR) have safety and efficacy comparable to traditional in-person cardiac rehabilitation, however, older adults are under-reported with effectiveness, feasibility, and usability remains unclear. METHODS: The study randomized 43 older adults (84 % males) to the 12-week CTR intervention or standard of care. Guided by Social Cognitive Theory, participants received individualized in-person assessment and e-coaching sessions, followed by CTR usage at home. Data were collected at baseline (T0), six-week (T1), and 12-week (T2). RESULTS: Participants in the CTR intervention group showed significant improvement in daily steps (T1: β = 4126.58, p = 0.001; T2: β = 5285, p = 0.01) and health-promoting lifestyle profile (T1: β = 23.26, p < 0.001; T2: β = 12.18, p = 0.008) across study endpoints. Twenty participants completed the intervention, with 40 % used the website for data-uploading or experiential learning, 90 % used the pedometer for tele-monitoring. Improving awareness of rehabilitation and an action focus were considered key facilitators while physical discomforts and difficulties in using the technology were described as the main barriers. CONCLUSIONS: The CTR is feasible, safe and effective in improving physical activity and healthy behaviors in older adults with CHD. Considering the variation in individual cardiovascular risk factors, full-scale RCT with a larger sample is needed to determine the effect of CTR on psychological symptoms, body weight and blood pressure, and quality of life.
Keywords: Older adults; Pilot; Coronary heart disease; Randomized controlled trial; Cardiac telerehabilitation